Pengaruh Intellectual Capital dan Corporate Social Responsibility terhadap Nilai Perusahaan dimoderasi oleh Kinerja - Rilla Gantino; Leli Ruliati Alam (Faculty of Economic and Business, 2020)
Competitive advantage through the use of knowledge and creating a good image through CSR activities is needed to face competition. Many companies have moved from resource based to knowledge base. Companies that are able to innovate and are able to create a good image will make consumers loyal and have an impact on improving performance. Increased performance will provide hope for investors and potential investors towards the company so that the company's value will increase, which is indicated by rising stock prices. This study aims to analyze the effect of intellectual capital and corporate social responsibility on firm value with company performance as a moderator variable in the basic and chemical industries listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. Hypothesis testing results showed that simultaneous intellectual capital and corporate social responsibility affect the value of the company, partially intellectual capital affects the value of the company and financial performance succeeded in moderator the relationship between them, corporate social responsibility affects the company value, in addition simultaneously financial performance succeeded in moderator the relationship between intellectual capital and corporate social responsibility to the value of the company, partially financial performance succeeded in moderator the relationship between intellectual capital to the value of the company, while partially financial performance was not able to moderate the relationship between cororate social responsibility and corporate value.